2013
DOI: 10.1002/jqs.2627
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Quaternary Rhine–Meuse dynamics in the southern North Sea: architecture, seismo‐lithofacies associations and malacological biozonation

Abstract: Mapping the Middle to Upper Pleistocene Rhine–Meuse sequence in the southern North Sea based on new core and seismic data has allowed a detailed palaeoenvironmental re‐assessment. An integrated seismo‐lithostratigraphic and malacological biostratigraphic framework is correlated with the optically stimulated luminescence‐dated Rhine–Meuse sequence onshore. The data point to a dynamic interplay of fluvial and marine systems in the southern part of the North Sea driven by longer‐term (>100 ka) tectonic and epeiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Based on studies from the southern North Sea it can be concluded that both scarps are believed to be remnants of ancient river terraces of the Rhine and Meuse rivers (Bridgland & D'Olier, 1995;Busschers et al, 2005Busschers et al, , 2007Busschers et al, , 2008Gibbard, 1995;Hijma et al, 2012;Peeters, Busschers, & Stouthamer, 2015;Rijsdijk et al, 2013). This conclusion is similar to what Mathys (2009) suggested about the Offshore Platform being the valley floor of an incised river valley.…”
Section: Planation Surfaces Escarpments and Slope Breakssupporting
confidence: 54%
See 1 more Smart Citation
“…Based on studies from the southern North Sea it can be concluded that both scarps are believed to be remnants of ancient river terraces of the Rhine and Meuse rivers (Bridgland & D'Olier, 1995;Busschers et al, 2005Busschers et al, , 2007Busschers et al, , 2008Gibbard, 1995;Hijma et al, 2012;Peeters, Busschers, & Stouthamer, 2015;Rijsdijk et al, 2013). This conclusion is similar to what Mathys (2009) suggested about the Offshore Platform being the valley floor of an incised river valley.…”
Section: Planation Surfaces Escarpments and Slope Breakssupporting
confidence: 54%
“…This has import implications for future palaeogeographical reconstructions of the area (e.g. Busschers et al, 2005Busschers et al, , 2007Busschers et al, , 2008Hijma et al, 2012;Peeters et al, 2015;Rijsdijk et al, 2013). Farther north the Thornton Valley connects to the Northern Valley (see Main map).…”
Section: Palaeovalleysmentioning
confidence: 96%
“…According to Hijma et al (2012), that would mean that these fossils must have been transported. A study by Rijsdijk et al (2013) also considers 14 C dates anomalously young, based on marine taxa dates obtained by racemization.…”
Section: Case Study Discussion: the North Seamentioning
confidence: 99%
“…Mollusc assemblages of the Holocene, Eemian and older interglacial North Seas differ in composition, aiding their stratigraphical distinction (e.g. Meijer & Preece, 1995; Rijsdijk et al, 2013). For archaeology, it is mostly the degree to which marine ravinement eroded terrestrial palaeosurfaces that matters.…”
Section: Landforms and Other Morpho-sedimentary Featuresmentioning
confidence: 99%